The Impact of Ginger on Alleviating Motion Sicknes - Tariq, Muhammad; Khan, Sikandar Ali; Malik, Muhammad Sheraz Afzal; Chandio, Muzafar Ahmad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association of beneficial effects of Ginger on motion sickness.Study Design: Quasi-Experimental study.Place and Duration of Study: Aero-Medical institute Pakistan Air force Masroor base, Karachi Pakistan, from May to Oct 2019.Methodology: Quasi- Experimental study was carried out on 60 pilots, divided into two groups control and a trial group. Thirty pilots were randomly placed in each group. Both groups were matched, control group was served with placebo juice whereas trial group was served with ginger juice to drink. Both groups were placed in a simulator to induce motion sickness. Later on they were asked to fill a simulator sickness questionnaire. Responses were analyzed in Statistical Package for Social Sciences version 20.Results: In Control group 19(63.3%) of individuals experienced motion sickness and 11(36.7%) did not experience motion sickness whereas in trial group only 9(29.8%) individuals experienced motion sickness while 21(70.2%) of individuals did not experience motion sickness.Conclusion: Ginger is more effective in reducing motion sickness as compared to placebo. It shows that individuals of trial group showed good response to ginger as compared to placebo in control group.